PENGARUH LINGKUNGAN SEKOLAH TERHADAP PRILAKU KEAGAMAAN PESERTA DIDIK TP 2023-2024 DI MAN 1 BUKITTINGGI - Yen Happy Rahmi; Mustafa Mustafa; Albaihaqi Anas; Deswalantri Deswalantri (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This The issue addressed in this research is the extent to which the school environment influences the religious behavior of students in Phase F at MAN 1 Bukittinggi. The school environment includes physical facilities, the quality of teaching, school culture, interactions between students and teachers, as well as programs that support the development of character and religious behavior. This study aims to determine whether the educational environment at MAN 1 Bukittinggi impacts the religious behavior of students in Phase F, where the students have had enough interaction with the school environment and have a better understanding of the learning atmosphere at the school. The research approach used is a quantitative correlational method, which aims to determine whether there is a relationship between the variables studied. The sampling technique used is purposive sampling. Data collection was carried out through questionnaires, observations, and documentation. Data analysis was conducted using the SPSS software application with descriptive statistical testing. Based on the results of the research, it can be concluded that there is a significant positive influence between the school environment and religious behavior, with a correlation coefficient value of 0.440. This value is classified as moderate according to correlation coefficient guidelines, indicating that the better the educational environment at the school, the more prominent the religious behavior practiced by the students. Therefore, this study proves that a supportive educational environment can contribute to enhancing students' religious behavior.